Relationship between Phenolic and Antioxidant Concentration of Humulus lupulus and Alpha Acid Content. (3rd April 2019) - Elrod, Susan M.; Langley, Caroline; Greenspan, Phillip; Hofmeister, Erik
Abstract: It has been well established that beer is an excellent source of polyphenols, due in part to the contribution of xanthohumol and other compounds from hops. The intent of this study was to explore the relationship between alpha acid content, antioxidant activity, and boil time in hops. Ten hops strains with different alpha acid contents were analyzed for phenolic antioxidant content via Total Phenolic Concentration (TPC) and Ferric Reducing Antioxidant Power (FRAP) assays. Each strain was boiled for 10, 30, or 60 min, consistent with typical beer brewing protocols. Phenolic and antioxidant content increased with boil time, with Citra hops showing higher phenolic content than other strains regardless of boil time. It appears that longer boil times yield higher TPC and FRAP concentrations regardless of alpha acid content. There was a nonstatistical inverse correlation between alpha acid and phenolic content; as a result, beers that use high alpha acid hops or short boil times may have lower TPC and FRAP concentration than beers that use low alpha acid hops and long boil times.